2012
DOI: 10.1007/s11033-012-2243-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of CAST gene polymorphisms with carcass and meat quality traits in Yanbian cattle of China

Abstract: Bovine calpastatin (CAST) gene polymorphisms have been associated with meat tenderness traits; however, little is known about how the CAST gene affects beef quality traits. In this study, 25 single nucleotide polymorphisms were detected in the CAST gene using polymerase chain reaction with single-strand conformation polymorphism and gene sequencing. Different preponderant genotypes were found at the corresponding gene locus. The E1-1, E1-2, and C3-1 loci were correlated with meat tenderness height and highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
1
14
0
3
Order By: Relevance
“…Curi et al (2010) evaluated carcass and meat traits in Bos indicus and Bos taurus-Bos indicus cross beef cattle using CAST SNPs. Furthermore, Li et al (2013) detected the CAST gene and found 25 SNPs, of which the E1-1, E1-2, and C3-1 loci were correlated with meat tenderness height and were highly correlated with fatty acid and amino acid content. However, the E4-2 locus was not correlated with meat tenderness; it was correlated with cooking loss, brightness, and yellowness, among other traits (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curi et al (2010) evaluated carcass and meat traits in Bos indicus and Bos taurus-Bos indicus cross beef cattle using CAST SNPs. Furthermore, Li et al (2013) detected the CAST gene and found 25 SNPs, of which the E1-1, E1-2, and C3-1 loci were correlated with meat tenderness height and were highly correlated with fatty acid and amino acid content. However, the E4-2 locus was not correlated with meat tenderness; it was correlated with cooking loss, brightness, and yellowness, among other traits (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Li et al (2013) detected the CAST gene and found 25 SNPs, of which the E1-1, E1-2, and C3-1 loci were correlated with meat tenderness height and were highly correlated with fatty acid and amino acid content. However, the E4-2 locus was not correlated with meat tenderness; it was correlated with cooking loss, brightness, and yellowness, among other traits (Li et al, 2013). The exon 28 genotypes of CAST showing allele frequencies of C (0.429) and T (0.571) were found to be significantly associated with calpastatin activity and Warner-Bratzler Shear Force (Chung and Davis, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…CAST gene is located on the fifth chromosome of sheep and have significant effect on meat tenderness by inhibiting calpaines in post mortem process (Kawasaki and Kawashima 1996;Juszczuk-Kubiak et al 2009;Khederzadeh 2011). Previous studies have also determined the relations of CAST gene and meat quality and carcass traits in livestock animals (Morris et al 2006;Zhou and Hickford 2008;Pinto et al 2010;Li et al 2013). Morever, many studies reported the associations of CAST gene with average daily weight…”
Section: Intrоduсtiоnmentioning
confidence: 99%
“…Em geral, cor de carne não é levada em conta nos programas de melhoramento genético relacionados à qualidade de carne bovina, mas a maioria dos pesquisadores de carne têm medido as variáveis de cor e, em alguns estudos, associações com marcadores moleculares têm sido testadas (LI et al, 2013;MELUCCI et al, 2012;PINTO et al, 2011;REARDON et al, 2010;RIBECA et al, 2012).…”
Section: Aspectos Gerais Relacionados Com Cor De Carneunclassified
“…Indivíduos contendo maiores concentrações O gene MC1R é um dos principais responsáveis pela regulação de melanina na pele de bovinos (ADALSTEINSSON et al, 1995;KLUNGLAND et al, 1995;ROUZAUD et al, 2000ROUZAUD et al, , 2003, enquanto o gene DBP está associado com as diferenças nas concentrações dos metabólitos da vitamina D 3 no plasma de humanos (ENGELMAN et al, 2008;KURYLOWICZ et al, 2006;SINOTTE et al, 2009). Por sua vez, o gene CAST está associado com maciez e cor de carne (CASAS et al, 2006;LI et al, 2013;MELUCCI et al, 2012;PINTO et al, 2010PINTO et al, , 2011REARDON et al, 2010;RIBECA et al, 2012;SCHENKEL et al, 2006 imediatamente submetido à centrifugação de 1.000 × g por 15 minutos para a obtenção do plasma, que foi então congelado à 20C até a realização das análises.…”
Section: Introductionunclassified